Rural Marketing Strategies in India: Recent Trends - Sneha R; Bibi Hajira (PT FORMOSA CENDEKIA GLOBAL, 2022)
In today’s competitive market environment all the companies are trying to maximise their growth and profits. Each and every company has its own marketing strategies. Marketing strategies are different for different markets. Rural Marketing Strategies are totally different from Urban Marketing Strategies. In order to survive in the market one has to tap both urban market as well as rural market. In this paper researcher discussed about various opportunities, threats, different market strategies in rural markets in India. Researcher also throw the light on recent trends in Rural Marketing.